Hubungan Pengetahuan Dan Pendidikan Ibu Dengan Status Gizi Balita Di Puskesmas Padang Garugur Kabupaten Padang Lawas Tahun 2024 - Halimatun Syakdiyah Harahap; Victorwan Novri Zendrato (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
The factors that influence the nutritional status of children under five are very substantial to be studied. This aims to find out what factors are related so that power action and efforts to improve nutrition can be taken in the community. Because health is a form of human right which is explicitly mandated by the 1945 Constitution. Education and time for mothers and the health of parents, especially mothers, are one of the causes of malnutrition in toddlers. This study aims to determine the relationship between maternal characteristics and the nutritional status of children under five at the Padang Garugur Public Health Center, Padang Lawas Regency. The research procedure was by measuring body weight, mothers of children under five were given a nutritional status questionnaire. Data analysis using the Chi-square test showed that from 45 samples. The majority of children's nutritional status is good (77.8%). There is a relationship between mother's knowledge and nutritional status of children under five at the Padang Garugur Public Health Center, Padang Lawas Regency (p = 0.001). There is a relationship between maternal education and the nutritional status of children under five at the Padang Garugur Health Center, Padang Lawas Regency (p = 0.005). From the results of the study, it can be concluded that knowledge, , education of mothers are related to the nutritional status of children under five. It is recommended that all mothers continue to seek information about children's health, especially the procedure for providing nutritious food to toddlers."